Effectiveness of temple-based stroke education program for risk reduction and promoting appropriate emergency response after acute stroke among Buddhist elderly in Uttaradit province Thailand - Onwilasini Stewart (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2012